A coupled system of nonlocal fractional differential equations with coupled and uncoupled slit-strips integral boundary conditions - Ahmad, B.; Ntouyas, S.K. (Нелінійні коливання, 2016)
This paper is concerned with the existence and uniqueness of solutions for a coupled system of fractional differential equations with coupled and uncoupled slit-strips integral boundary conditions. The existence and uniqueness of solutions is established by Banach’s contraction principle, while the existence of solutions is derived by using Leray – Schauder’s alternative. The results are explained with the aid of examples. Розглядається iснування та єдинiсть розв’язкiв з’єднаних систем нелокальних диференцiальних рiвнянь дробового порядку зi з’єднаними та нез’єднаними розщепленими смугами в iнтегральних граничних умовах. Iснування та єдинiсть розв’язкiв встановлено за допомогою теореми Банаха про стискаючi вiдображення. Iснування розв’язкiв доведено з використанням альтернативи Лерея – Шаудера. Результати пояснено за допомогою прикладiв.